Special Tables on Scheduled Tribes, Part VII (II), Vol-I, Series-11 - Banthia, J.K. (Karnataka, 1991)
Distribution of scheduled tribes population by sex, Main workers classified by industrial category age and sex for scheduled Tribes, Marginal workers classified by industrial category educational level and sex for scheduled tribes, Occupational classification of main and marginal workers other than cultivators and agricultural labourers by sex among scheduled Tribes, Age sex and marital status for scheduled tribes.
Keywords: Tables on Houses and Household Amenities